Land pawning practice in Semoyo Village, Patuk Sub-District, Gunungkidul Regency - Widihastuti, Setiati; Choirunnisa, Mita (Universitas Negeri Yogyakarta, 2023)
This study utilizes a qualitative approach to examine the customary practice of land pawning in Semoyo Village. This practice is based on traditional institutions passed down for generations. It involves the direct transfer of land without the need for a written agreement, witnesses, or village officials. The spirit of togetherness and trust in neighbors and relatives facilitate this practice. The borrower surrenders possession of the land to the lender, who can redeem the land within an agreed-upon time frame. In reality, land pawning has been a common practice in Semoyo Village for decades, as landowners have been unable to redeem their land. While the land is under pawn, the borrower has the right to possession and use. However, the land pawning practice in Semoyo Village is susceptible to disputes and coercion, despite being regulated by Article 7 of Law Number 56 PRP of 1960. Nonetheless, Semoyo Village residents continue to practice land pawning for various reasons, such as urgent needs, avoiding selling their land, difficulty obtaining loans from banks, mutual assistance, and obtaining additional cultivation land. Land pawning is only conducted among close neighbors or trusted relatives whose character is well-known.